Lymphogranuloma venereum: "a clinical and histopathological chameleon?" Linfogranuloma venéreo: "um camaleão clínico e histopatológico?" - Georgi Tchernev; Cristina Salaro; Mariana Carvalho Costa; James W. Patterson; Pietro Nenoff (Sociedade Brasileira de Dermatologia, 2010)
Lymphogranuloma venereum is an infection caused by a variety of the bacterium Chlamydia trachomatis. Both genital and extragenital manifestations of the disease can cause serious differential diagnostic difficulties, indirectly leading to progression and dissemination of the infection. This work describes cases of patients with lymphogranuloma venereum showing atypical clinical and/or histopathological findings. It also focuses on alternative therapeutic approaches, such as surgical excision at stage 1, that may lead to a positive outcome. It is not completely clear whether histopathological findings of lymphogranuloma venereum can reveal progression or changes in the course of the disease over time, as is the case in other diseases. We conclude that both clinical and histopathological observations in a larger number of patients are needed in order to further evaluate the findings presented in this article. Linfogranuloma venéreo é uma infecção causada por um tipo específico da bactéria Chlamydia trachomatis. Manifestações genitais e extragenitais da doença podem causar uma série de dificuldades no diagnóstico diferencial, indiretamente levando a progressão ou disseminação da infecção. Este trabalho apresenta casos de pacientes com linfogranuloma venéreo cujos achados clínicos e/ou histopatológicos são atípicos, além de abordar métodos de terapia alternativos, tais como excisão cirúrgica na fase 1, os quais podem trazer um resultado positivo. Ainda não se sabe se achados histopatológicos do linfogranuloma venéreo podem revelar progressão ou mudanças no curso da doença ao longo do tempo, como ocorre com outras enfermidades. Concluímos que observações clínicas e histopatológicas devem envolver um número maior de pacientes a fim de avaliar os resultados clínicos deste trabalho.